The Relationship of Knowledge, Parental Support and Self-Acceptance with the Level of Anxiety of Young Women in Facing Puberty at Junior High School 7 Jambi City in 2022 - Tikayani Manik, Manuella; Novita Eka Rini, Willia; Lanita, Usi; Ena Sari, Rumita; Sari, Puspita (Jurnal KESANS : Kesehatan dan Sains, 2023)
Introduction: Puberty is a phase of physical and psychological changes. Changes experience by adolescent can cause anxiety. Teenages girl are aware of their development that can cause anxiety, because of that, they need sufficient knowledge, support from their parents and a good concept of self-acceptance, so they are can be ready for puberty. Obective: The purpose of this study was to determine the relationship between knowledge, parents support, self-acceptance and anxiety levels in JHS 7 Jambi City.  Method: The study was conducted using a cross-sectional design with a sample size of 161 respondents. Statistical test using chi square test. Result and Discussion: Correlation between knowledge and anxiety levels was obtained (p-value <.001), correlation between parents support and anxiety levels was obtained (p-value <.020), correlation between self-acceptance and anxiety levels was obtained (p-value <.001).  Conclusion: Teenages girl have less knowledge that is as much 123 respondent (76.4%), teenages girl have negative parents suport that is as much 118 respondent (73.3%), teenages girl have low self-acceptance that is as much 125 respondent (77.6%). There was a significant correlation between knowledge, parents support and self-acceptance with anxiety levels